Problems improvement of professional competence of social worker (The Journal of Psychology and Sociology, 2013)
In this article, shall be reported to the problems of training and improving the skills of social workers in Kazakhstan, discusses contemporary social problems of society, the ways and means of addressing them. As well as the professional qualifications of the identity of a social worker and the requirement for a specialist. Describes the different job requirements to the social worker.
Keywords: . social work; professional ethics; morality; conscience; justice; humanism; values of civiliza-tion; social technologies; social assistance; applied science; legal protection.